PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE LENOVO DENGAN LOYALITAS PELANGGAN SEBAGAI VARIABEL INTERVENING (STUDI KASUS DI RW001 KELURAHAN GROGOL SELATAN KEBAYORAN LAMA) - Rifaldy, Aulia Rizki (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2024)
The purpose of this study is to determine the effect of brand image, product quality and price on purchasing decisions with customer loyalty as an intervening variable. The total population in this study amount to 3,750 populations. The sample obtained was 110 respondents. As independent variables, namely brand image, product quality, and price, while the dependent variable is a purchase decision, and the intervening variable is customer loyalty. The method of data collection is done by questionnaire. While the data processing and analysis method used is the Path Analysis test using the Amos Version 22.0 software. This research was conducted on residents of RW001, Grogol Selatan Village, Kebayoran Lama, South Jakarta. The results of the analysis obtained p-value for the first hypothesis of 0.356> alpha 0.05. Thus Ho1 is accepted and Ha1 is rejected which means that there is no significant effect between brand image on customer loyalty, for the second hypothesis is 0.000 <alpha 0.05. Thus Ho2 is rejected and Ha2 is accepted, which means that there is a significant effect between product quality on customer loyalty, for the third hypothesis is 0.893> alpha 0.05. Thus Ho3 is accepted and Ha3 is rejected, which means that there is no significant effect between price and customer loyalty, for the fourth hypothesis is 0.000 <alpha 0.05. Thus Ho4 is rejected and Ha4 is accepted, which means that there is a significant influence between customer loyalty to purchasing decisions, to hypothesize the five standardized direct effects of brand image on purchasing decisions through customer loyalty has a value (0.125). and the value of the standardized indirect effect of brand image on purchasing decisions through customer loyalty (0.030). It can be concluded that the value of standardized direct effect (0.125)> value of standardized indirect effect (0.030). Thus Ho5 is rejected and Ha5 is accepted which means that the brand image has a direct effect on purchasing decisions through customer loyalty, for the sixth hypothesis the standardized direct effect price of purchasing decisions through customer loyalty has a value (0.239) and the value of standardized indirect effect prices on purchase decisions through loyalty customer is (0.004). It can be concluded that the value of standardized direct effect (0.239)> standardized indirect effect value (0.004). Thus Ho6 is rejected and Ha6 is accepted, which means that prices affect the purchasing decisions through customer loyaltyl.